2001
DOI: 10.1038/sj.bjp.0704339
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of palmitoylethanolamide on gastrointestinal motility in mice

Abstract: 1 We have studied the eect of palmitoylethanolamide (PEA, 2.5 ± 30 mg kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 25 publications
(41 reference statements)
4
83
0
Order By: Relevance
“…In the present study, we investigated the contribution of NAAA to CFAinduced joint inflammation and the effects of the b-lactambased NAAA inhibitor ARN726 in this model. We found that administration of CFA into the paw of rats causes a substantial decrement in the tissue content of PEA and OEA, as previously shown in other animal models of inflammation (Capasso et al, 2001;De Filippis et al, 2009;Solorzano et al, 2009) and in patients suffering from rheumatoid arthritis (Richardson et al, 2008). Along with changes in PEA and OEA, we found that CFA produces a marked local elevation in the catalytically active form of NAAA, which is produced by self-cleavage of the inactive holoenzyme (Tsuboi et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, we investigated the contribution of NAAA to CFAinduced joint inflammation and the effects of the b-lactambased NAAA inhibitor ARN726 in this model. We found that administration of CFA into the paw of rats causes a substantial decrement in the tissue content of PEA and OEA, as previously shown in other animal models of inflammation (Capasso et al, 2001;De Filippis et al, 2009;Solorzano et al, 2009) and in patients suffering from rheumatoid arthritis (Richardson et al, 2008). Along with changes in PEA and OEA, we found that CFA produces a marked local elevation in the catalytically active form of NAAA, which is produced by self-cleavage of the inactive holoenzyme (Tsuboi et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…For example, the PEA content in exudates from mice exposed to carrageenan is substantially lower than that of exudates obtained from naive mice (Solorzano et al, 2009). Similarly, tissue PEA levels are reduced in carrageenan-induced granuloma (De Filippis et al, 2009) and in the intestine of mice treated with croton oil (Capasso et al, 2001;Izzo et al, 2012). Experiments in the macrophage-like RAW264.7 cell line, suggest that the decrease in PEA and OEA accumulation results from transcriptional suppression of N-acyl-PEphospholipase D expression, which is negatively controlled by activators of Toll-like receptor 4 (Zhu et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Stimulation with proinflammatory agents such as LPS or carrageenan decreases PEA content in various cells and tissues of rodents, including intestine (Capasso et al, 2001), skin (LoVerme et al, 2005), and leukocytes (Endocannabinoid Research Group et al, 2010;Solorzano et al, 2009). Adding clinical relevance to these findings, it was shown that synovial fluid from patients with rheumatoid arthritis and osteoarthritis contains lower amounts of PEA compared with control subjects (Richardson et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Behavioral effects produced by activation of central CB 1 receptors include reduced locomotion and body temperature, catalepsy, alterations in memory, sedation, and euphoria-effects that are also commonly observed with recreational marijuana use (Adams and Martin, 1996). In the periphery, activation of CB 1 receptors on nerve endings produces analgesia (Calignano et al, 1998;Jaggar et al, 1998), reduces cough (Calignano et al, 2000), and inhibits intestinal transit (Capasso et al, 2001). The functions served by CB 2 receptors are less clear, but recent evidence suggests that they may modulate immune cell function (Klein et al, 2001) to produce peripheral analgesia and anti-inflammation Malan et al, 2003;Quartilho et al, 2003)-although the mechanism by which these phenomena occur remains enigmatic.…”
Section: Cannabinoid Receptorsmentioning
confidence: 99%